Neonatal Mortality in an Urban Population in Ibadan, Nigeria - Anthony O. Adetola; Olukemi O. Tongo; Adebola E. Orimadegun; Kike Osinusi (Pediatrics and Neonatology)
Neonatal mortality remains a major contributor to death among children younger than 5 years in developing countries. This study was undertaken to determine the neonatal mortality rate (NMR), causes of death, and associated risk factors among hospital live births in a suburban population in Nigeria. Patients and Methods: A total of 1058 consecutive live newborns at Adeoyo Maternity Hospital, Ibadan, were enrolled at birth and followed up in their homes for 28 days. The causes of death were extracted from hospital records, and verbal autopsy was used to determine the causes of death outside the hospital. Results: The NMR was 32.1 per 1000 live births. The leading causes of death were severe perinatal asphyxia (79.4%), low birth weight (LBW: 55.9%), and infections (41.2%). The associated risk factors were lack of antenatal care [relative risk (RR)=45.18; 95% confidence interval (CI)=7.80, 261.60]; prolonged rupture of membranes (RR=4.47; 95% CI=1.95, 10.25); maternal peripartal fever (RR=5.42; 95% CI=2.35, 12.52); prematurity (RR=7.53; 95% CI=4.91, 11.55); and LBW (RR=5.50; 95% CI=3.88, 7.80). Conclusion: NMR is high among hospital live births in Ibadan. There is a need for programs encouraging the use of antenatal care, improving skills on neonatal resuscitation and care of LBW infants; as well as implementation of community-based newborn survival strategies.